The dream that never dies: the ideals and realities of cosmopolitanism in science, 1870–1940 - Robert Fox (Studia Historiae Scientiarum)
In the half-century before the Great War, collaborative international ventures in science became increasingly common. The trend, manifested in scientific congresses and attempts to establish agreement on physical units and systems of nomenclature, had important consequences.